1998
DOI: 10.1038/bjc.1998.199
|View full text |Cite
|
Sign up to set email alerts
|

High suicide mortality soon after diagnosis among cancer patients in central Italy

Abstract: Summary A high suicide mortality risk has been documented among a population-based cohort of 27 123 cancer patients resident in central Italy where the general suicide rate is low. Forty-one suicides were observed (SMR = 2.36) which were only 0.2% of all deaths. However, the highest risk (SMR = 27.7) during the first 6 months after diagnosis, represents a greater contrast with the general population than has been observed in other studies.Keywords: suicide; mortality An increased suicide risk has been shown fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
53
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 9 publications
8
53
0
1
Order By: Relevance
“…For males, the RR was 1.38 (95% CI: 1.12 -1.68), and for females it was 1.74 (95% CI: 1.36 -2.19) ( Table 6). Previous studies conducted in non-UK countries, or regions of countries, have demonstrated similarly altered RRs of suicide (either when codified as DSH, or when DSH events are assessed in combination with events of undetermined intent) for male cancer patients in the 1.3 -2.8 range, and for female cancer patients in the 0.5 -2.7 range (Louhivuori and Hakama, 1979;Fox et al, 1982;Allebeck et al, 1989;Allebeck and Bolund, 1991;Levi et al, 1991;Crocetti et al, 1998;Tanaka et al, 1999;Innos et al, 2003;Yousaf et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For males, the RR was 1.38 (95% CI: 1.12 -1.68), and for females it was 1.74 (95% CI: 1.36 -2.19) ( Table 6). Previous studies conducted in non-UK countries, or regions of countries, have demonstrated similarly altered RRs of suicide (either when codified as DSH, or when DSH events are assessed in combination with events of undetermined intent) for male cancer patients in the 1.3 -2.8 range, and for female cancer patients in the 0.5 -2.7 range (Louhivuori and Hakama, 1979;Fox et al, 1982;Allebeck et al, 1989;Allebeck and Bolund, 1991;Levi et al, 1991;Crocetti et al, 1998;Tanaka et al, 1999;Innos et al, 2003;Yousaf et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been reported in many of the non-UK cancer-suicide studies consistent with the greatest psychological morbidity occurring on diagnosis (Louhivuori and Hakama, 1979;Fox et al, 1982;Allebeck et al, 1989;Allebeck and Bolund, 1991;Levi et al, 1991; Storm et al, Note: Owing to the inclusion of both primary and secondary field information in the hospital admission data, a single event resulting in admission may appear within 41 subcategory of harm. 1991; Crocetti et al, 1998;Tanaka et al, 1999;Innos et al, 2003;Yousaf et al, 2005). Suicide in the setting of cancer may, for example, be more associated with hopelessness than depression per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential explanation for that finding could be related to the timing of suicide. The risk of suicide is felt to be strongest very early after diagnosis [14][15][16]33 . Fang et al 15 found that the highest risk fell within the first 12 weeks after diagnosis (relative risk: 4.7) and that the risk lessened after that time (relative risk at 12-52 weeks: 2.1; relative risk at 52 weeks and beyond: 1.6).…”
Section: Discussionmentioning
confidence: 99%
“…1 The first year after diagnosis and especially the first 3 months are associated with an increased risk. 2 A second smaller peak is between 12 and 14 months following diagnosis and is possibly the result of either disease progression or failure of treatment. 3 Suicide in the general population seems as an extreme manifestation of failure to cope with chronic distress, whereas in cancer patients, acute stressors that severely affect quality of life such as pain, physical impairment, depression, and loss of independence and autonomy are often the triggers for suicidal action.…”
mentioning
confidence: 99%